KRIMINALISASI KEBIJAKAN - Priyatno, Dwidja (Sekolah Tinggi Hukum Bandung, 2010)
Legal protection, especially against the alleged criminalization policies, which apply to policy makers and implementers, should be explicitly included in the legislation, as an excuse criminal eraser, ie eliminate unlawful nature (justification). However, its implementation should be done with reference also to some general principles of state governance, namely: the principle of legal certainty, is a principle in law that gave priority to state the basis of legislation, decency and fairness in every policy of state officials, the principle of Orderly Operation of the State, is a principle that to order, harmony, and balance in the control of the state organization, the principle of public interest, is the principle of priority to public welfare by aspirational, accommodative and selective, the principle of openness, is the principle of opening up to the right of people to obtain correct, honest and not discriminatory on the administration of the state with due regard to protection of personal rights, class and state secrets, the principle of proportionality, is a principle that prioritizes a balance betweenrights and obligations of the state, the principle of professionalism, expertise is a principle that prioritizes based code of ethics and rules of law and regulations, and principles akuntabililas, is a principle which determines that each activity and the end result of the activities of stateadministration must be accountable to the community or the people as the supreme sovereign state in accordance with the provisions of the legislation in force, also refers to the principles unwritten law which is the propriety of living in society. During the signs are obeyed, then thecriminalization of policy, will not do.Keywords: Criminalization Policies - Public Policy - Crimes Against Public Interest